2017
DOI: 10.18632/oncotarget.23051
|View full text |Cite
|
Sign up to set email alerts
|

YAP regulates PD-L1 expression in human NSCLC cells

Abstract: Programmed death-ligand 1 (PD-L1) is a membrane protein on tumor cells that binds to the PD-1 receptor expressed on immune cells, leading to the immune escape of tumor cells. Yes-associated protein (YAP) is a main effector of the Hippo/YAP signaling pathway, which plays important roles in cancer development. Here we show that YAP regulates PD-L1 expression in human non-small cell lung cancer (NSCLC) cells. First, we investigated YAP and PD-L1 expression at the protein level in 142 NSCLC samples and 15 normal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 50 publications
14
97
0
Order By: Relevance
“…Indeed, the expression of miR-130a mimic or miR-130a sponge suppressed or enhanced VGLL4 and PD-L1 levels, respectively, in A549 cells (Fig 6A-C). Consistent with previous reports Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018), we observed an increased PD-L1 mRNA level when YAP5SA, a transcriptionally active and Hippo pathway-resistant YAP mutant, was expressed in A549 cells (Fig EV5B). Consistent with previous reports Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018), we observed an increased PD-L1 mRNA level when YAP5SA, a transcriptionally active and Hippo pathway-resistant YAP mutant, was expressed in A549 cells (Fig EV5B).…”
Section: Yap Inhibits Ifnc-inducible Pd-l1 Expressionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, the expression of miR-130a mimic or miR-130a sponge suppressed or enhanced VGLL4 and PD-L1 levels, respectively, in A549 cells (Fig 6A-C). Consistent with previous reports Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018), we observed an increased PD-L1 mRNA level when YAP5SA, a transcriptionally active and Hippo pathway-resistant YAP mutant, was expressed in A549 cells (Fig EV5B). Consistent with previous reports Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018), we observed an increased PD-L1 mRNA level when YAP5SA, a transcriptionally active and Hippo pathway-resistant YAP mutant, was expressed in A549 cells (Fig EV5B).…”
Section: Yap Inhibits Ifnc-inducible Pd-l1 Expressionsupporting
confidence: 92%
“…Furthermore, expression of YAP target genes CTGF and CYR61 was slightly decreased by inhibition of miR-130a ( Fig 6D), while knockdown of VGLL4 slightly increased miR-130a expression ( Fig EV5A), confirming the positive feedback loop of YAP-miR-130a-VGLL4 axis. Consistent with previous reports Lee et al, 2017;Miao et al, 2017;Janse van Rensburg et al, 2018;Kim et al, 2018), we observed an increased PD-L1 mRNA level when YAP5SA, a transcriptionally active and Hippo pathway-resistant YAP mutant, was expressed in A549 cells ( Fig EV5B). However, we detected a strong inhibition on ◀ Figure 3.…”
Section: Yap Inhibits Ifnc-inducible Pd-l1 Expressionsupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Figure5B, YAP/ TAZ knockdown prevented TGFβ stimulated PD-L1 expression in both human and murine fibroblasts, consistent with previous reports that PD-L1 is a direct transcriptional target of YAP/TAZ in several tumor models. [47][48][49]…”
Section: Yap/taz Regulates Pd-l1 Expression By Tgfβmentioning
confidence: 99%